Impact of Microfinance Lending On Economic Growth of Third world Nations: Study of Nigeria - Obasi, Nwele James; Chukwuka, Ogbonna Innocent; Akwawa, Uduimo Anthony (International Journal of Business, Economics and Management, 2014)
This paper examines the impact of microfinance lending on the Nigerian economic growth. Specifically, the study sought to evaluate how microfinance lending to micro, small and medium scale enterprises in Nigeria has impacted on changing the business fortunes of the poor and hence the Nigerian economy. Primary and secondary data were collected and analysed using programme designs, numerical structure response in implementation and performance model in a bid to delineate the relationship between microfinance loans and growth of micro, small and medium scale enterprises in Nigeria. Our results reveal that the microfinance loans have not gone deep enough to ensure a clean break from community and commercial banking practices.